Tahawwul Ath-Thariqah At-Tijaniyyah fi Al-Maahid Al-Haditsah Inda Ra'yi Biter Albaghir - Kuswandi, Iwan; Tobroni, Tobroni; In'am, Akhsanul; Khozin, Khozin; Majid, Ach Nurholis (el Harakah: Jurnal Budaya Islam, 2021)
ركز الباحث إلى أن يبحث شأن الطريقة التيجانية من شكل التخارج الذي قام به الشيخ جوهري والشيخ تيجاني والشيخ أحمد فوزي لكونهم ممارسين للطريقة التيجانية في معهد الأمين الإسلامي برندوان، وجميعهم قادة المعهد ورؤساء الأمور في فتراتهم الخاصة. يستخدم هذا البحث دراسة ظاهرية، مع طرق جمع البيانات للرصد والمقابلات والتوثيق، ويتم تحليل نتائج البحث باستخدام نظرية بناء الواقع الاجتماعي لبيتر إل بيرغر. وأخيرا حصل الاستنتاج على أن البناء الذي قام به المشايخ الثلاثة المقدمة في المعهد مشير إلى نفس الأهداف أي تخريج الطلاب المتفوقين في الدين من استيعاب القيم والشخصيات النبيلة، مثل التوبة، والصدق، والصبر، والتقوى، والاستقامة، والامتنان، والورع، والزهد، والتواضع، من خلال التدريس المستمر للكتب الصوفية، وتقديم الحياة المثالية لطلابهم دائما. بالنسبة إلى أن الشيوخ الثلاثة لديهم أشكال ولهجات مختلفة. حيثما قاد الشيخ جوهري بشكل فردي، بينما من فترة الشيخ تيجاني إلى الشيخ أحمد فوزي تم تشكيل مجلس الرياسة، والذي نفذ الإدارة الحديثة والقيادة الجماعية. أشرك الشيخ جوهري الطلاب في الطريقة التيجانية، باختلاف ما لم يحث عليه الاثنان الآخران الطلاب على اتباع الطريقة التيجانية. This study constructs the form of externalization performed by Kiai Djauhari, Kiai Tidjani, and Kiai Ahmad Fauzi as practitioners of the Tijaniyah Order at the Al-Amien Prenduan Islamic Boarding School, all of which are leaders and caregivers based on their respective periods. Moreover, while this is phenomenological-based research, its data collection methods appear to consist of observation, interviews, and documentation. Furthermore, the research findings are analyzed through the theory of Social Reality Construction of Peter L Berger. In accordance with the conclusion, it revealed that the construction carried out by the three Kiais at the Islamic Boarding School possesses the same meaning, namely to produce mutafaqquh fiddin students by internalizing noble values and characters such as repentance, honesty, patience, god-fearing piety (taqwa), steadfastness (istiqamah), gratitude, abstinence (wara’), asceticism (zuhud’), sincerity and humility by continuously teaching the books of Sufism as well as providing an exemplary life for their students. However, the three of them have different forms and accentuations. While Kiai Djauhari seemed to lead individually, either Kiai Tidjani or Kiai Ahmad Fauzi appeared to lead by forming a Riasah Council which implemented modern management and collegial leadership in their respective periods. In addition, while Kiai Djauhari involved students in practicing the Tijaniyah Order, it seemed that the other two did not encourage students to do so.